They are terms of an algebraic expression that can be simplified to: 3x+9 or factored to 3(x+3)
Chat with our AI personalities
First add coefficients: * 1x + 1x = 2x Second add the other values: * 4 + 5 = 9 Put it all together!: * 1x + 1x + 4 + 5 = 2x +9 * 2x + 9
2x + 1 = 1x + 11Subtract 1x from each side:1x + 1 = 11Subtract 1 from each side:1x = 10
Simplifying x2 + -2x + -63 Reorder the terms: -63 + -2x + x2 Factor a trinomial. (-7 + -1x)(9 + -1x) Final result: (-7 + -1x)(9 + -1x)
The expression "negative x plus 3x" can be simplified by combining like terms. Negative x can be written as -1x, so the expression becomes -1x + 3x. When you combine -1x and 3x, you get 2x. Therefore, the simplified expression is 2x.
There is always a 1 in front of the x but the 1 is invisible so it same as 1x + 1x = 2x x + x = 2x